2011
DOI: 10.1101/gad.1998611
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoinositide [PI(3,5)P2] lipid-dependent regulation of the general transcriptional regulator Tup1

Abstract: Transcriptional activity of a gene is governed by transcriptional regulatory complexes that assemble/disassemble on the gene and control the chromatin architecture. How cytoplasmic components influence the assembly/ disassembly of transcriptional regulatory complexes is poorly understood. Here we report that the budding yeast Saccharomyces cerevisiae has a chromatin architecture-modulating mechanism that is dependent on the endosomal lipid PI(3,5)P 2 . We identified Tup1 and Cti6 as new, highly specific PI(3,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
56
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 64 publications
5
56
0
Order By: Relevance
“…These observations are consistent with Wang et al and Krishna et al who also showed that mTORC1 retains its activity in PIKfyve-abrogated cells (Wang et al, 2015;Krishna et al, 2016). We considered the possibility that mTORC1 and starvation controls PIKfyve activity instead, which may then modulate TFEB, perhaps by a PtdIns(3,5)P 2 -dependent localization of TFEB to lysosomes, as has been shown for Tup1, a transcription factor in yeast that controls galactose metabolism (Han and Emr, 2011). Yet, we could not observe a significant decrease in PtdIns(3,5)P 2 levels in mTOR-inhibited cells, though we cannot exclude disruption of a specific pool of PtdIns(3,5)P 2 or of PtdIns(5)P, a lipid that is directly or indirectly synthesized by PIKfyve (Zolov et al, 2012;Sbrissa et al, 2012).…”
Section: Pikfyve and Tfeb Regulationsupporting
confidence: 79%
“…These observations are consistent with Wang et al and Krishna et al who also showed that mTORC1 retains its activity in PIKfyve-abrogated cells (Wang et al, 2015;Krishna et al, 2016). We considered the possibility that mTORC1 and starvation controls PIKfyve activity instead, which may then modulate TFEB, perhaps by a PtdIns(3,5)P 2 -dependent localization of TFEB to lysosomes, as has been shown for Tup1, a transcription factor in yeast that controls galactose metabolism (Han and Emr, 2011). Yet, we could not observe a significant decrease in PtdIns(3,5)P 2 levels in mTOR-inhibited cells, though we cannot exclude disruption of a specific pool of PtdIns(3,5)P 2 or of PtdIns(5)P, a lipid that is directly or indirectly synthesized by PIKfyve (Zolov et al, 2012;Sbrissa et al, 2012).…”
Section: Pikfyve and Tfeb Regulationsupporting
confidence: 79%
“…and associate with internal membranes, resulting in modification of its gene expression function (Han and Emr 2011). It is possible that Mig1 and Mig2 are modified in some way by associating with Msb2, Opy2, Ste7, or Kss1, which results in alteration of their normal function.…”
Section: Mig1 and Mig2 Proteins Connect Glucose Signaling To Mapk Regmentioning
confidence: 99%
“…Our previous study on the yeast galactose metabolism gene, GAL1, identified a novel phosphatidylinositol 3,5-bisphosphate (PI(3,5)P 2 ) 2 -dependent transcriptional regulatory mechanism (12). PI(3,5)P 2 is a phosphoinositide lipid that is synthesized from phosphatidylinositol 3-phosphate by the Fab1 phosphatidylinositol-3-phosphate 5-kinase at the late endosomal/vacuolar lysosomal membranes (13,14).…”
mentioning
confidence: 99%